PENERAPAN MANAJEMEN OPERASIONAL PAKET WISATA TAILOR MADE TOUR DI PT. TUNAS INDONESIA TOURS AND TRAVEL YOGYAKARTA - Rahmat Abdullah; Yunita Prihastuti (STIE Pariwisata API Yogyakarta, 2022)
This research aims to determine the application of operational management of tailor made tour packages at PT. Tunas Indonesia Tours Travel Yogyakarta. This research used a qualitative descriptive approach, the data were collected through observation, interviews and literature studies. The informants in this research are the company's staffs who are involved in, command or understand the operational management of tour packages. Data analysis used the model of Miles and Huberman, namely data reduction, data display and conclusion drawing. The results of the research showed there are four operational stages of tailor made tour packages making by Travel Consultant staff, the first stage is the planning stage consists of receiving the package tour reservations, following up the package tour reservations, determining payment policies according to company regulations, and issuing travel documents for the tour. The next stage, the organizing stage is conducting in tour preparation proceed. The directing stage is taking out during the tour. And the last stage, the controlling stage is taking out by the travel consultant staff during the post-tour evaluation.